2020
DOI: 10.3390/polym12030729
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Poplar Fiber/PLA Composites: Comparison on the Effect of Maleic Anhydride and KH550 Modification of Poplar Fiber

Abstract: To improve the interfacial adhesion and dispersion of a poplar fiber in a polylactic acid (PLA) matrix, maleic anhydride (MA) and a silane coupling agent (KH550) were used to modify the poplar fiber. The poplar fiber/PLA composites were produced with different modifier contents. The mechanical, thermal, rheological, and physical properties of composites were investigated. A comparison of different natural fiber modifications on the properties of composites was also analyzed. The results showed that both MA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Recently, it has been observed that studies on thermoplastic polymer reinforced with wood/plant fibers have become widespread. In addition, it has been found that the properties of composites (such as interfacial adhesion and thermal properties) were improved as a result of the addition of modified wood/plant fibers to the polymer matrix (Csizmadia et al 2013;Wei et al 2013;Spiridon et al 2016;Zhang et al 2017;Narlıoğlu 2018;Yang et al 2020). The compatibility of PLA polymer was improved after plant fibers were treated with silane coupling agent (KH-550) (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been observed that studies on thermoplastic polymer reinforced with wood/plant fibers have become widespread. In addition, it has been found that the properties of composites (such as interfacial adhesion and thermal properties) were improved as a result of the addition of modified wood/plant fibers to the polymer matrix (Csizmadia et al 2013;Wei et al 2013;Spiridon et al 2016;Zhang et al 2017;Narlıoğlu 2018;Yang et al 2020). The compatibility of PLA polymer was improved after plant fibers were treated with silane coupling agent (KH-550) (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Ti–O–B band appears at 1398 cm –1 , showing that TiO 2 nanoparticles have successfully reacted with H 3 BO 3 . 58 , 59 Furthermore, the peaks at 1346 and 1131 cm –1 refer to the absorption band of N–B 47 and the stretching vibration of Si–O–C, 60 , 61 verifying that KH550 has reacted with the PVA sponge and TiO 2 nanoparticles have been firmly anchored onto the skeletons of the PVA sponge. In addition, the observed peak at 1242 cm –1 is due to the stretching vibration of the C–F group, 61 , 62 revealing the chemical modification of FDTS on the TiO 2 –PVA sponge.…”
Section: Resultsmentioning
confidence: 93%
“…The increase may be due to good interfacial adhesion between fiber/matrix, the intact rigidity of the fiber during modification, and the interaction of the coupling agent with the fiber and the PLA. 37 However, when the sugarcane bagasse fiber with treatment and without treatment does not have MAPE, the flexural modulus goes down. This can be due to two contributions, the fact that the applied load cannot be transferred from the polymer matrix to the rigid fiber particles or the bad dispersion of fiber in the matrix.…”
Section: Resultsmentioning
confidence: 99%